Assessment of fluorescence polarization assay: A candid diagnostic tool in Brucella abortus strain 19 vaccinated areas - Kalleshamurthy, T.; Shekar, R.; Niranjanamurthy, H.H.; Natesan, K.; Shome, B.R.; Bambal, R.G.; Sairiwal, L.; Barbuddhe, S.B.; Sahare, A.; Kilari, S.; Rahman, Habibur; Shome, R. (Wiley, 2018)
Brucellosis caused by the bacteria of the genus Brucella is an important zoonosis and constitutes a serious public health hazard. Brucellosis is diagnosed mainly by the Rose Bengal plate test and indirect ELISA, both of which have poor specificity because false positive serological reactions occur when screening animals that have been vaccinated with B. abortus S19. Fluorescence polarization assay (FPA) was evaluated for screening samples from cattle and buffalo calves with persistent antibody titers induced by vaccination. The standardized FPA exhibited relative sensitivity and specificity of 0.94 and 0.95, respectively, and the area under the curve, kappa and accuracy were 0.98, 0.87 and 0.95, respectively. Comparison of competitive ELISA and FPA revealed that, FPA is more specific than competitive ELISA. The high specificity, sensitivity and 95% accuracy of FPA indicate that, it is suitable for testing vaccinated animals because it can distinguish between infected from vaccinated animals.